Enhancing self-care in hypertensive pregnant women through WhatsApp application - Rachmawati, Irma; Yanti Hermayanti; Ermiati, Ermiati (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2025)
Hypertension in pregnancy is currently the leading cause of maternal mortality. Self-care strategies, delivered via media adjusted to technological progress, accessibility, and pregnant women's needs, offer a practical means to manage this condition. represent a feasible option for the management of this condition. Because of its widespread use, WhatsApp could be used to improve self-care in hypertensive pregnant women. This study aims to determine the effect of WhatsApp on self-care in pregnant women with hypertension. A quasi-experimental pretest-posttest control group design. A total of 42 respondents were recruited by consecutive sampling from six community health centers, 21 respondents were in the intervention group and 21 respondents were in the control group. The outcomes were evaluated using the Hypertension Self-Care Profile (HBP-SCP) questionnaire, which was adapted for the Indonesian context and validated (r=0.517–0.957) and reliable (α=0.935) both before and after health education. Data analysis used nonparametric Wilcoxon matched-pairs and Mann-Whitney tests. In the intervention group, self-care scores improved significantly post-intervention (p<0.05), unlike the control group (p>0.05). The Mann-Whitney test confirmed a significant difference between groups (p<0.05).WhatsApp education boosted self-care scores, utilizing its accessibility and closed-group features for uniform information delivery. These findings advocate integrating such media into community health center protocols, bolstering health professional educational roles. Randomized trials on long-term adherence to WhatsApp-guided self-care protocols and studies comparing these to traditional in-person counseling recommended for future research.